2008
DOI: 10.1210/en.2007-1515
|View full text |Cite
|
Sign up to set email alerts
|

Increased Energy Expenditure Contributes More to the Body Weight-Reducing Effect of Rimonabant than Reduced Food Intake in Candy-Fed Wistar Rats

Abstract: The CB1 receptor antagonist, rimonabant, affects the endocannabinoid system and causes a sustained reduction in body weight (BW) despite the transient nature of the reduction in food intake. Therefore, in a multiple-dose study, female candy-fed Wistar rats were treated with rimonabant (10 mg/kg) and matched with pair-fed rats to distinguish between hypophagic action and hypothesized effects on energy expenditure. Within the first week of treatment, rimonabant reduced BW nearly to levels of standard rat chow-fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
95
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 42 publications
9
95
6
Order By: Relevance
“…This speculation is supported by recently published data that energy expenditure based on whole body fat oxidation measured by indirect calorimetry was increased during treatment with rimonabant in this animal model. 26 The differences observed in the patterns of LCACoAs, grouped as SFA, MUFA and PUFA, reflected only in part the ingredients of fatty acid species of the different diets. SFA and MUFA were elevated, similarly to their content in the candy-diet.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This speculation is supported by recently published data that energy expenditure based on whole body fat oxidation measured by indirect calorimetry was increased during treatment with rimonabant in this animal model. 26 The differences observed in the patterns of LCACoAs, grouped as SFA, MUFA and PUFA, reflected only in part the ingredients of fatty acid species of the different diets. SFA and MUFA were elevated, similarly to their content in the candy-diet.…”
Section: Discussionmentioning
confidence: 98%
“…It has recently been reported that increased energy expenditure based on increased fat oxidation contributed more to the sustained body weight reducing effect of rimonabant than reduced food intake. 26 The HepCL signal measured by MRS as about 9-10% of water signal corresponds to about 15 mg triglyceride per Visceral adiposity and rimonabant AW Herling et al gram of liver (1.5% liver fat) for the candy-diet control as well as for the rimonabant-treated group; this indicates that these values are far below a fatty liver (45% liver fat). In this study, no reduction of the HepCL (Figure 2c) was observed at the end of the study in the rimonabant candy-diet group.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…increased energy expenditure) mechanisms (Cota et al ., 2003; Jbilo et al ., 2005; Herling et al ., 2008; Nogueiras et al ., 2008). Whilst this present study did not permit us to discriminate between these two different modes of action directly, our findings indicate that rimonabant is unlikely to convey its metabolic improvements in aged mice by increasing energy expenditure.…”
Section: Discussionmentioning
confidence: 99%